PERTUMBUHAN KEMBALI DAN PRODUKSI BEBERAPA JENIS RUMPUT YANG DIBERI PUPUK ORGANIK - N.G.K. Roni; N.M. Witariadi; N.W. Siti; I.G. Suranjaya (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2016)
Production, quality and availability of forage one of which is determined by soil fertility and soil health. The use of chemical fertilizers (inorganic) in a period of time is one of the causes of land degradation (Kartini, 2007), application of organic fertilizers is the right step in maintaining soil fertility and soil health, and reduce the negative impact of the use of inorganic fertilizers. The study aimed to evaluate the response of regrowth and production of several species of grass to organic fertilizer conducted in a greenhouse using a completely randomized design split plot pattern 3 x 4 with three replications. The first factor (main plot / main plot) is a type of grass is Panicum maximum var. trichoglume (R1), Setaria splendida (R2), and Pennisetum purpureum (R3); The second factor (sub-plot / subplot) is a type of organic fertilizer that is without fertilizer (P0), manure (P1), compost (P2), and vermicompost (P3). The results showed that there was no interaction effect between type of grass with the type of organic fertilizer on the regrowth and production of grass Panicum maximum var. trichoglume, Setaria splendida, and Pennisetum purpureum. Treatment types of grass significant (P <0.05) on all observed variables, while the treatment of organic fertilizers only significant (P <0.05) in the variable number of tillers, number of leaves, stem dry weight, total dry weight of forage and leaf area per pot. Based on the results of this study concluded that there was no interaction effect between type of grass with organic fertilizer. The three types of grass have different productivity, highest growth in grass with vermicompost fertilizer and highest production in grass with compost fertilizer.Key words: Organic fertilizers, panicum grass, Setaria grass, elephant grass